The detection of 35delG mutation and environmental etiologic factors in cochlear implant users - doi:10.5020/18061230.2009.p69 - Camila Nogueira Lélis; Marília Fontenele e Silva Câmara; Edi Lúcia Sartorato (Universidade de Fortaleza, 2012)
Aim: To identify the occurrence of 35delG mutation and of environmental factors related to hearing loss in patients with cochlear implant, determining the functional gain post-implant. Methods: It was a cross-sectional study conducted with six volunteers, aged from five to twenty-one years old. The studied variables consisted on the identification of risk factors for hearing loss in prenatal, perinatal and postnatal periods. For genetic investigation, the occurrence of 35delG mutation in the connexin 26 gene was studied. The functional gain due to the implant was evaluated with "pure tone" stimulus in modulated frequencies of 250Hz, 500Hz, 1000Hz, 2000Hz, 3000Hz and 4000Hz. Results: In the study of environmental factors, we evidenced reports of TORCH infections (Toxoplasmosis, Rubella, Cytomegalovirus, Herpes and Syphilis), maternal hypertension, abortive usage, Meningitis, Measles, oxygen therapy and Jaundice. The genetic investigation revealed two cases of 35delG mutation, one in homozygosis and other in heterozygosis. The functional gain due to the cochlear implant ranged from 60 to 85dBHL. Conclusion: In the studied sample, both the occurrences of 35delG mutation and of environmental factors related to the hearing loss were evident. The values of functional gain were satisfactory, regardless from the etiology related to the loss.